The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.123421
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inhibition of α-glucosidase activity by bavachalcone

Abstract: Bavachalcone is an important active component of the traditional Chinese medicine Fructus Psoraleae. The inhibitory effect of bavachalcone on α-glucosidase activity is reported for the first time and the mechanism elucidated by molecular docking. The inhibition of α-glucosidase by bavachalcone (IC50 15.35 ± 0.57 μg/mL) was significantly superior to acarbose (IC50 2.77 ± 0.09 mg/mL). Inhibition type was mixed competitive and non-competitive. Molecular docking suggested this inhibition stems from hydrogen bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Aloe vera (L.) extracts showed potential AG and AA inhibitory activities, possibly through a competitive or non-competitive manner as reported by multiple studies in the same domain. [21,22] Hydro-ethanol (40:60) extract of Aloe vera (L.) possesses more efficacy in inhibiting the activities of said enzymes than other extracts considering acarbose as standard.…”
Section: Resultsmentioning
confidence: 99%
“…Aloe vera (L.) extracts showed potential AG and AA inhibitory activities, possibly through a competitive or non-competitive manner as reported by multiple studies in the same domain. [21,22] Hydro-ethanol (40:60) extract of Aloe vera (L.) possesses more efficacy in inhibiting the activities of said enzymes than other extracts considering acarbose as standard.…”
Section: Resultsmentioning
confidence: 99%
“…Trilobatin and GA can interact with the hydrophobic amino acids tryptophan and phenylalanine, which confirms that trilobatin and GA can bind to the active site of α-glucosidase hydrophobic, resulting in reduced fluorescence quenching. 62 In addition, the formation of hydrogen bonds may reduce hydrophilicity while increasing the hydrophobicity of α-glucosidase, which helps increase the stability of the complex. Compared to GA, trilobatin forms more hydrogen bonds with α-glucosidase by the individual glycosidic groups on the A ring, resulting in enhanced inhibition of α-glucosidase by CT. Hua et al showed that an increase in molecular size, polarity, and nonplanar structure may reduce the inhibition of α-glucosidase, 63 so the two glucuronic acids linked by glycyrrhizic acid may lead to steric obstruction and reduce the affinity for α-glucosidase.…”
Section: Molecular Docking Of Sweetener With α-Glucosidase and α-Amylasementioning
confidence: 99%
“…With increasing attention paid to the benefits for Qingzhuan Dark Tea's human bodies, such as reducing weight and fat (Monobe et al, 2008), antioxidant ability (Xia, 2019), improvement of intestinal function (Li, 2018), and bacteriostatic effect (Mao, 2019). One of the main components of Qingzhuan Dark Tea is Polysaccharides, which is also one of the main components that play its physiological role (Ting et al, 2019). At present-day, lots of studies have verified that polysaccharides from Qingzhuan Dark Tea have the antioxidant ability and competitive inhibition of α-glycosidase activity (Ting et al, 2019).…”
Section: Introductionmentioning
confidence: 99%